STIMULASI KETERAMPILAN BAHASA RESEPTIF ANAK MELALUI KEGIATAN MENDENGARKAN CERITA DI TK MIFTAHUL ULUM PANDAWANGI MALANG - Diana Ulfah; Endah Umiasih (Universitas Negeri Makassar, 2021)
Early childhood education is the initial foundation of all aspects of development that children have, one of which is language development. Language development is a very important aspect, especially in the ability to read. Receptive language is a child's ability to understand, hear and listen to information or understand meaning. Receptive language skills of children aged 3-6 years become the basis for expressing emotions, messages, socializing, and learning to the next stage of development. This study is to find out the children's receptive language skills through storytelling activities. This study is a class action study. The results of this study showed that there was an increase in the children's receptive language skills in the second cycle of listening to pictorial stories from 13 children. In listening activities there are 2 children developing as expected, 11 children develop very well. In the retelling activity there are 4 children developing as expected, 9 children develop very well.